Mahler: Music, Reception, Identity - PÉTERI, Lóránt (Studia musicologica, 2019)
Writings on the socio-cultural complexities of Mahlerʼs identity and his music in context vary in relation to four basic motifs: his Jewishness; his Germanness; the partly Slav environment of his early years; and his relationship to the Austro-Hungarian Dual Monarchy. Studies combine these elements, or privilege one above another. It may help to rethink this subject if we consider that his self-awareness formed amid a changing social environment; if his personal identity will be studied in the context of the identity history of his family; and through scrutinizing the decisive socializing role of the localities in which he lived. These conclusions can reveal the unparalleled mobility of his career in a rapidly-transforming context. Late nineteenth-century Central European societies drew at once on the “past” (post-feudal, pre-modern attitudes and practices), “present” (constitutionalism based on equal civilian rights, and nationalism), and “future” (populist and racist ideologies questioning the enlightened, liberal consensus). All three impacted not only Mahler᾿s identity, but his image: how the surrounding society perceived him. These approaches also facilitate critical readings of the contemporaneous attempts to embed Mahler’s music in national, regional, and ethno-cultural contexts. This paper examines the reception of the third movement of Symphony No. 1 as a case study, exploring how Mahler’s construed images were reflected in different interpretations of this music.